AN ANALYSIS OF ENTAILMENT FOUND ON COSMETIC AND FAS FOOD ADVERTISEMENT - Marnala Pangaribuan (JETAL: Journal of English Teaching & Applied Linguistic, 2022)
ABSTRACT: This research intended to find out the types of entailment found on advertisement of cosmetic and fast food. In conducting this research, the research use qualitative method with content analysis because the data were collected from document, in form of words and the explanation of the result. The researcher used note taking as instrument of this research in order to get the valid data. The findings showed that there are two types of entailment that used in cosmetic and fast food advertisement, those are: one-way entailment which occurs 10 times and two-way entailment which occurs 6 times. The dominant type of entailment on advertisement was one-way entailment with 10 times or 62.5%.